Masker Herbal Nephrolephis Exaltata Menghambat Pemanjangan Waktu Transpor Mukosilier Hidung Pekerja Industri Tekstil - Nurhayadi, Tommy; Prasetyo, Awal; Miranti, Ika Pawitra (Fakultas Kedokteran Universitas Trisakti, 2023)
Background Herbal masks are made from lamination-spraying of Nephrolepis exaltata (NE) extract on regular medical masks, which may absorb Volatile Organic compounds (VOC) in the occupational exposure of the textile industry'sindustry's dyeing area. Therefore, clinically, the effect on nasal mucociliary transport time (TMSH) needed to be tested and compared with ordinary cloth-mask teens used by textile industry workers as their daily personal protective equipment. Methods Pre- and post-test randomized control trials on 30 textile-dyeing areas of textile industry workers in Bawean Indonesia, divided into two groups; 1) users of NE herbal masks (N=17) as the treatment group and 2) regular cloth mask users (N=13) as control-group, for eight weeks. First, the TMSH time (seconds) was carried out before and after treatment using the saccharin test by an ENT specialist, followed by a different test on delta. Results The TMSH-time of NE herbal mask users before vs after treatment was 1169.60 ± 644.55 seconds vs 1075.75 ± 677.36 (p = 0.102). On subjects wearing regular cloth masks was 1113.75 ± 479.43 vs 1187.40 ± 544.96 (p = 0.003). The mean delta'sdelta's difference before and after treatment was 25.5 seconds, with a significant difference in mean delta TMSH-time between the treatment and control groups (p = 0.048). Conclusions Textile-industry workers who wear NE herbal masks have better TMSH times than regular cloth mask wearer